2022
DOI: 10.3389/fcvm.2022.1046560
|View full text |Cite
|
Sign up to set email alerts
|

The impact of high-intensity interval training on vascular function in adults: A systematic review and meta-analysis

Abstract: AimWe performed a systematic review and meta-analysis to investigate the effects of high-intensity interval training (HIIT) compared with moderate-intensity continuous training (MICT) or with no exercise (CON) on vascular function in adults who were free of cardiometabolic diseases and those with cardiometabolic diseases.MethodsA search across three electronic databases including Scopus, PubMed, and Web of Science was conducted through February 2022 to identify the randomized trials evaluating HIIT vs. MICT an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 97 publications
0
9
0
Order By: Relevance
“…The effects of AE on central cardiovascular adaptations and arterial function remain poorly understood after stroke. However, in adults with cardiovascular and cardiometabolic conditions, HIIT is superior to MICT for improving measures of cardiac contractility and systolic function,108 and endothelial function 109. In stroke, preliminary evidence suggests that higher intensity AE can improve diastolic function (eg, right atrial emptying fraction) compared with usual care,71 and that HIIT is more effective than MICT for improving systolic function (eg, cardiac output) 60.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of AE on central cardiovascular adaptations and arterial function remain poorly understood after stroke. However, in adults with cardiovascular and cardiometabolic conditions, HIIT is superior to MICT for improving measures of cardiac contractility and systolic function,108 and endothelial function 109. In stroke, preliminary evidence suggests that higher intensity AE can improve diastolic function (eg, right atrial emptying fraction) compared with usual care,71 and that HIIT is more effective than MICT for improving systolic function (eg, cardiac output) 60.…”
Section: Discussionmentioning
confidence: 99%
“…However, in adults with cardiovascular and cardiometabolic conditions, HIIT is superior to MICT for improving measures of cardiac contractility and systolic function, 108 and endothelial function. 109 In stroke, preliminary evidence suggests that higher intensity AE can improve diastolic function (eg, right atrial emptying fraction) compared with usual care, 71 and that HIIT is more effective than MICT for improving systolic function (eg, cardiac output). 60 HIIT can also elicit acute increases in novel arterial biomarkers, including insulin-like growth factor one and vascular endothelial growth factor, compared with MICT.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…However, different modalities of physical activity can be considered. Although intermittent exercise appears to be particularly interesting compared with continuous activity when endothelial function is studied in healthy subjects [ 41 ], this discrepancy is not always observed when the effects of different modalities of exercises are evaluated in the context of I/R whether in human [ 39 ] or animal [ 42 ] studies. When looking more specifically at the endothelial consequences of ischemia-reperfusion, the work of Thijssen et al demonstrated a protective effect of physical activity independent of the type of exercise [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plyometric exercises are established and valid methods to induce muscle-damage and inflammatory responses [18,19]. From this perspective, plyometric exercise under hypoxia might have the ability to further stimulate pro-inflammatory cytokine release [20,21], for inducing additional muscular adaptive processes.…”
Section: Introductionmentioning
confidence: 99%